H5N2 Highly Pathogenic Avian Influenza Viruses from the US 2014-2015 outbreak have an unusually long pre-clinical period in turkeys. Issue 1 (December 2016) - Spackman, Erica; Pantin-Jackwood, Mary; Kapczynski, Darrell; Swayne, David; Suarez, David
Abstract Background From December 2014 through June 2015, the US experienced the most costly highly pathogenic avian influenza (HPAI) outbreak to date. Most cases in commercial poultry were caused by an H5N2 strain which was a reassortant with 5 Eurasian lineage genes, including a clade 2.3.4.4 goose/Guangdong/1996 lineage hemagglutinin, and 3 genes from North American wild waterfowl low pathogenicity avian influenza viruses. The outbreak primarily affected turkeys and table-egg layer type chickens. Three isolates were selected for characterization in turkeys: the US index isolate from December 2014 (A/northern pintail/WA/40964/2014), and two poultry isolates from April 2015 (A/chicken/IA/13388/2015 and A/turkey/MN/12528/2015). Results Four week old broad-breasted white turkeys were inoculated with one of three doses (102, 104 or 106 50% egg infectious doses [EID50 ] per bird) of each of the isolates to evaluate infectious dose and pathogenesis. The mean bird infectious dose of A/northern pintail/WA/40964/2014 and A/turkey/MN/12528/2015 was 105 EID50 per bird, but was 103 EID50 per bird for A/chicken/IA/13388/2015, suggesting the latter had greater adaptation to gallinaceous birds. All three isolates had unusually long mean death time of 5.3–5.9 days post challenge, and the primary clinical signs were severe lethargy and neurological signs which started no more than 24 h before death (the average pre-clinical period was 4 days). Infected turkeys also shed high levels of virus by both the oropharyngeal and cloacal routes. Conclusions The unusually long mean death times, high levels of virus in feces, and increased adaptation of the later viruses may have contributed to the rapid spread of the virus during the peak of the outbreak.